Methods of the current situation analysis in the regional education, research, and innovation markets in order to establish the strategic development program for universities - Gusarova, Miroslava S (2021)
The article describes the experience of forming a strategic development program by analyzing the current situation and identifying possible forms of interaction between the University and the region. By analyzing the strategic development documents of the Region and documents of the Ministry of Education and Science towards subordinate institutions, statistical data on the situation in the regional market of education, science, innovation, the potential of the university, the article reports on its results and the possibility of effective partnership with the authorities and the largest corporations of the region and the country in training and retraining of personnel and scientific research, considering the development trends of the region. In conclusion, the reform of Tyumen Industrial University is timely and relevant. However, the article also highlights a number of problems related to both the further development of the university's brand and the need to adjust the development to the demand of the region to expand training and retraining programs, develop new technologies in the oil and gas business, and building materials and structures. The results allow for drawing up a program for the strategic development of the university in a more qualitative and deep way.